Cutaneous manifestations of breast cancer - Agnieszka B. Owczarczyk-Saczonek; Dawid Sigorski; Paweł Różanowski; Agnieszka Markiewicz; Waldemar J. Placek (Termedia Publishing House, 2017)
Breast cancer is the most common malignant neoplasm among women in Poland and in the European Union. According to most recent data of the Polish National Cancer Registry, in 2014 breast cancer was diagnosed in over 17,000 women. Based on the National Health Fund records, it is estimated that there are about 55,000-60,000 women in Poland who have a history of breast cancer diagnosis and are potentially at a risk of relapse. The most common sign of breast cancer is the presence of a nodule, however women also seek medical attention because of skin lesions. The aim of the study is to present diverse clinical manifestations of direct infiltrates and/or skin metastases of breast cancer. Attention is drawn to the importance of including breast cancer in the differential diagnosis of skin lesions.